Social Media Addiction and Healthy Lifestyle among Post Graduate Students: A Social Work Perspective - Shobana, P; Actovin, C Arul; Alam, Iftekhar (International Journal of Social Sciences and Management, 2023)
Digital Technology growth has unprecedentedly impacted daily life, providing opportunities and engendering challenges for professional social work practice. Social media, as an interactive technology, allows people to communicate and exchange ideas in the forms of images and videos with others not in their immediate vicinity. The present study aims to study the relationship between social media addiction and healthy lifestyle practices among postgraduate students from a social work perspective. The descriptive research design was used for this cross-sectional study conducted among 111 postgraduate students of Pondicherry University. The questionnaire includes a socio-demographic profile, a social media addiction scale, and a healthy lifestyle screening tool. According to the findings, most (66.7 per cent) respondents have a medium addiction to social media. Most (64.9 per cent) respondents follow a healthy lifestyle to a moderate extent. A significant association exists between social media addiction and a healthy lifestyle. The students are highly vulnerable, at the threshold of high addiction levels, and their lifestyle might become susceptible and precarious. Social workers may play a pivotal role in using Information, Education, and Communication (IEC) to bring behavioural change among the youth.